Características produtivas e valor nutritivo de duas variedades de Cana-de-Açúcar com e sem a adubação foliar de Silício - DAMASCENO, Paulo Junio Silva (2023)
The objective of this study was to evaluate the effect of foliar fertilization with Si (FFSi) on sugarcane in different aspects, including agronomic performance, technological quality of juice, and nutritional value of forage, as well as losses during storage in piles and ensilage. The sugarcane varieties RB867515 and RB962962 were used, which were propagated through Pre Budded Seedlings. FFSi was carried out at 64 days after transplanting, using a sodium silicate solution as the source of silicon. Harvesting of sugarcane plants took place at 16 months, while ratoon cane was harvested at eight months after the last cutting. Agronomic characteristics and productivity were measured for both cycles, and the technological quality of juice was obtained only for the sugarcane plants. The randomized block design (RBD) in a 2 x 2 factorial scheme was used: two FFSi treatments (with and without) and two varieties. Each treatment was replicated four times in four blocks. topped canes (TP) and canes connected to the pointers (CP). Two trials were performed, the storage in piles and the ensiling trial. In the storage trial, a completely randomized design (CRD) was used in a split plot scheme in time, with five repetitions. Sugarcane was stored in piles for different periods (0, 2, 4, 6, and 8 days), and the nutritional value and losses of green matter (LGM) were evaluated at each period. The ensilage assay followed a CRD in split-plots, with four repetitions. The nutritional value and losses of the silage were evaluated 60 days after ensilage. The in situ ruminal degradability of dry matter in 24 hours (DMD24h) and the undegraded neutral detergent fiber in organic matter in 288 h (uNDFom%NDF) were evaluated in a RBD with three blocks (cows). The application of FFSi in the sugarcane plants of the RB962962 variety resulted in a 35% increase in stalk productivity and dry matter production. However, the RB867515 variety, which naturally has 50% higher sucrose productivity, experienced an 18% reduction when exposed to FFSi. Silicon-fertilized plants showed a 7% reduction in sugar recovery. An increase of 22% in silicon content in the sugarcane plants was observed due to the application of FFSi. Regarding ratoon cane, FFSi reduced stalk productivity in the RB867515 variety by 21%, but increased it by 26% in the RB962962. The LGM during storage in piles gradually increased up to the 6th day, regardless of FFSi. FFSi had a positive effect on reducing LGM in the RB867515 variety stored with the pointers, where, after two days from cutting, LGM was up to 40% lower. FFSi favored a higher recovery of dry matter in the silage of RB962962, but had the opposite effect in RB867515. The DMD24h and uNDFom of fresh stalks, stalks stored in piles, and ensiled stalks were not negatively affected by the presence of FFSi in both varieties. In conclusion, FFSi can increase sugarcane productivity, although it reduces the technological quality of the juice. Additionally, FFSi promotes the preservation of sugarcane stored in piles for up to eight days during the dry season. Furthermore, ensilage of sugarcane plants fertilized with foliar Si may achieve less deterioration in the silo. The in situ degradability of dry matter in 24 hours and the undegraded neutral detergent fiber in organic matter in 288 hours of fresh sugarcane stalks, stalks stored in piles, and ensiled stalks are not negatively affected by FFSi.